In-home cannabis smoking more prevalent than in-home tobacco smoking among 2019 Global Drug Survey respondents. (February 2022) - Bellettiere, John; Liles, Sandy; Posis, Alexander Ivan B.; Anuskiewicz, Blake; Tripathi, Osika; Nguyen, Benjamin; Chavez, Paul; Zhu, Shu-Hong; Park, Ji-Yeun; Winstock, Adam; Ferris, Jason
Highlights: Recently, cigarette use has declined while cannabis use has increased. Smoking cannabis produces second- and third-hand emissions that may impact health. Comparisons of in-home cannabis and tobacco smoking have not been available. In-home smoking of cannabis was more prevalent than tobacco. Global cannabis acceptability movements urge research on use patterns & health effects. Abstract: Purpose of the Research: Early evidence from studies of home smoking policies suggests that in-home cannabis smoking is more often allowed than in-home tobacco smoking, but there are not yet data on whether cannabis is more often smoked in the home compared to tobacco, or whether in-home cannabis and tobacco smoking differs by usage status. Using cross-sectional data from over 100, 000 sentinel drug users from 17 countries, we compared cannabis and tobacco smoking in the homes of Global Drug Survey 2019 respondents who currently used cannabis only, tobacco only, both tobacco and cannabis, or neither. Principal Results: Complete data on cannabis and tobacco use and in-home smoking were available for 107, 272 adults (average age = 30 ± 12, 34% women, countries with the three highest response rates; Germany = 32%, USA = 10%, New Zealand = 9%). In total, 53.6% and 50.6% of respondents reported past-year cannabis and tobacco smoking in their home respectively. Stratifying respondents into current cannabis-only users, tobacco-only users, dual users, and non-users, past-year in-home cannabis smoking was more prevalent (78.8%) among cannabis-only users than was in-home tobacco smoking (67.9%) among tobacco-only users. Among dual users, past-year in-home cannabis smoking (82.8%; 95%CI = 80%-86%) was higher than in-home tobacco smoking (75.9%; 95%CI = 69%–81%; p < 0.001). In-home cannabis and tobacco smoking was similar among non-users (20.2% and 20.5%, respectively). Major Conclusions: Past-year in-home cannabis smoking was more prevalent than tobacco smoking in the homes of participants who used cannabis and/or tobacco, supporting our speculation that in-home cannabis smoking might be more socially acceptable than in-home tobacco smoking.